Trisomy 8 presentation by inflammatory manifestations and its response to thalidomide: two case reports and narrative review - Zhang, Xiaohua; Zhao, Yan; Pan, Yuting; Jin, Jing; Fan, Zhidan; Yu, Haiguo (Frontiers in Pediatrics, 2024)
Abstract: Objective: It has been recognized that there is a nexus among Trisomy 8 (T8), Behcet's disease (BD), and myelodysplastic syndrome (MDS). We reported a series of inflammatory features in 2 children with T8 without hematological involvement. Methods: 2 children with trisomy 8 who were excluded from MDS were retrospectively collected from the Department of Rheumatology and Immunology, Children’s Hospital of Nanjing Medical University, Nanjing. Results: Patients developed a range of inflammatory manifestations before a diagnosis of T8. The clinical manifestations of T8 patients vary from normal to severely disabled. Glucocorticoids and thalidomide can effectively relieve inflammation in patients with T8. Conclusion: The early clinical manifestations of T8 in children lack specificity, and the diagnosis is mainly based on karyotype analysis, gastrointestinal endoscopy and bone marrow aspiration findings. Active and effective immunoregulatory therapy and long-term follow-up can improve the prognosis of patients with T8.